A Virtual Inhibition of Anti-diabetic Activity of Bioactive Compounds in Harp (Sandoricum koetjape (Burm. f.) Merr.) - Elvina Rashida Khairi; Rahmi Izzati; Raissa Kendra Ainiyah; Salma Wahid Marseti; Nuraini Rosyadah; Turhadi Turhadi; Fatchiyah Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2023)
The prevalence of type 2 diabetes mellitus (DMT2) has increased worldwide over the last 3 decades. This prompted the researchers to consider the medical benefits of plants, including harp (Sandoricum koetjape). In Indonesia, harp is a common medicinal herb used to cure fever, colic, vaginal discharge, diarrhea, and bloating. harp also contains substances like flavonoids, tannins, or quinones that have anti-diabetic properties. This study aims to determine the potential compound from the harp plant in inhibiting the breakdown of sugar using molecular docking to minimize the buildup of sugar in the blood. Bioactive compounds of harp were obtained from earlier studies and collected from KNApSAcK database. The physicochemical properties of the compounds were analyzed by using SwissADME and PASS Online. Using the CB-Dock server and the receptors α-amylase and α-glucosidase retrieved from RCSB PDB, along with acarbose as a control, the selected compounds were examined for their molecular interactions and binding affinities. Molecular interactions were visualized using Biovia Discovery Studio 2019. The result showed that three compounds were discovered to show potential as antidiabetic medicines out of the 54 active compounds that were screened using SwissADME. Those three compounds are sandorinic acid A, sandorinic acid B, and quercetin with the absolute value of free binding energy ranging from -7.2 to -9.6 kcal/mol. By targeting residues found in amylase and glucosidase, sandorinic acid A, sandorinic acid B, and quercetin have binding sites that are similar to acarbose. The three bioactive compounds quercetin, sandorinic acid a, and sandorinic acid b that are found in harp are expected to have the potential to be agents of type 2 diabetes mellitus.